Fake Populism or Real Populism: Pork Barrel Policy as Political Corruption in House of Representative During 2009-2013 - Wasisto Raharjo Jati (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2013)
This article aims to analyze the practice of pork barrel politics in the level of Indonesia legislature tiers and its political management campaign. Since 2004, electoral democracy already delegate to the common people to chosen their representation directly through general election in the level executive and legislative. Those conditions oblige politician and political parties to approaching the commons in order to obtain their vote and popularize both actors into public. The paradigm of research is a pork barrel politics. This paradigm supports to understand and analyze the corruption symptoms i.e. politico corruption in legislative tier and electoral-corruption in political-campaign which become chronic problems in this country. Result of research has showed populism is pivotal key which triggered up politician and parties to corruption in order to persist their political tenure and funding their political cost in pursue to re-elect again in second office terms. No matter their corruption practice that implicate to budgeting fraud. Both actors take political favor to disguise within social aids following the governmental policy, so that, they hindered from corruption accusation. Finally, this paper wants to recommend legal improvement into our budgeting cycle wherein there are public participation to watch it and moral improvement to politician and parties to reducing their corruption if they wants to become truly populist politician figure into public.